Predictors of depression and malnutrition among older persons attending primary healthcare centres in South Western Nigeria - Babatunde Akodu; Samuel Akinwunmi; Temitope Ladi-Akinyemi; Ibukunoluwa Baiyeroju; Adebayo Onajole (Journal of Clinical Sciences, 2023)
Background: Malnutrition and depression have been found to be prevalent in the older persons and often lead to preventable adverse complications. Depression has been shown to be associated with malnutrition. This study was aimed at determining the predictors of depression and malnutrition among older persons attending selected primary health-care centers (PHC) in Kosofe local government area in Lagos, Nigeria. Methods: This was a descriptive cross-sectional study carried out among older persons attending PHC in Kosofe local government, Lagos. A multi-stage random technique was used to select the 219 participants from the PHC centers. Data were collected using a structured interviewer-administered questionnaire and analyzed using Epi Info 7.1. Chi-square was used to test the association between Socio-demographic characteristics and nutritional status, body mass index and depression, and one-way ANOVA was used to test for the association between anthropometric parameters and malnutrition. Associations were statistically significant if P < 0.05. Results: It was found that 57.9% were malnourished or at risk of malnutrition. The study showed that 47.1% of the participants were depressed. There was a significant association (<0.001) between the malnutrition and the level of depression. There was a statistically significant association between family support (P ≤ 0.001), malnutrition (P ≤ 0.001), and depression. There was statistically significant association between the height (P = 0.009), weight (P = 0.001), waist–hip ratio (P = 0.036), and the malnutrition. Remarkably, there was statistically significant association between the waist (P = 0.023) and hip circumference (P = 0.047) and their level of depression. Conclusion: The results from this study revealed a high prevalence of malnutrition and depression among older persons. Therefore, health providers working in PHC centers should have a high index of suspicion for depression among older persons with malnutrition.